Forest products industry in Indonesia is now facing major issues such as a huge log deficit, a low industrial efficiency, and a declined in forest products competitiveness. Production cost and optimization analysis are then conducted to provide insight for the firms so they can operate efficiently and have high products competitiveness. The results show that a production cost varies from US$ 193.60 per m3 to US$ 247.68 per m3 with an average of US$ 214.50 per m3 and a firm’s profit would increa - Bintang SIMANGUNSONG; Endartya Nur SOLIHAH (Jurnal Ilmu dan Teknologi Hasil Hutan, 2009)
Forest products industry in Indonesia is now facing major issues such as a huge log deficit, a low industrial efficiency, and a declined in forest products competitiveness.  Production cost and optimization analysis are then conducted to provide insight for the firms so they can operate efficiently and have high products competitiveness. The results show that a production cost varies from US$ 193.60 per m3 to US$ 247.68 per m3 with an average of US$ 214.50 per m3 and a firm’s profit would increase by 18% even though production decreased by 1.5% when the firm operates at optimum level.   Keywords :    Plywood industry, optimization, production cost analysis, competitiveness